Claiming place : biracial young adults of the post-civil rights era - Kilson, Marion, 1936- (Westport, Conn. : Bergin & Garvey, 2001)
Annotation Born on the crest of the Civil Rights Movement but coming-of-age at a time when biraciality was less widely acknowledged than it is at the opening of the new century, the participants in this project represent a transitional generation of Biracial Americans who share existential realities in a society dominated by White culture. These existential commonalties include ambiguous racial identities, color conundrums, and rejection by both people of color and European Americans. Nevertheless, biracial young adults'personal views and experiences are diverse.
Annotation Based on 52 interviews with biracial men and women, Kilson (State Salem College) discusses their experiences in childhood, with their families, with lovers, and with friends. She also addresses the development of racial identity, the choices biracial adults make about their identities, and the way these identities shape and impact their lives. A separate section presents the actual statements those interviewed made in reply to questions on these matters. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Part I. Biracial American Experience in the Post-Civil Rights Era -- Biracial Americans -- Biracial Americans and Their Families -- Biracial American Identity Choices -- Racial Realities in Adult Biracial American Lives -- Biracal American Life Themes -- Part II. Biracial American Voices -- Development of Racial Identities -- Childhood Memories of Race -- Family Relationships Remembered -- Assessments of Biracial American Experiences -- Epilogue -- Bibliography -- Index.
Includes bibliographical references (pages 175-186) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Multiracial people -- Race identity -- United States; Multiracial people -- United States -- Social conditions -- 20th century; Young adults -- United States -- Social conditions -- 20th century; United States -- Race relations; Jeunes adultes -- États-Unis -- Conditions sociales -- 20e siècle.; États-Unis -- Relations raciales; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Multiracial people -- Social conditions; Race relations; Multiracial people -- Race identity; Young adults -- Social conditions; United States; Interethnische Herkunft; Ethnische Beziehungen; USA; 1900-1999